2019
DOI: 10.1007/s00401-018-01956-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinal α-synuclein deposits in Parkinson’s disease patients and animal models

Abstract: Despite decades of research, accurate diagnosis of Parkinson's disease remains a challenge, and disease-modifying treatments are still lacking. Research into the early (presymptomatic) stages of Parkinson's disease and the discovery of novel biomarkers is of utmost importance to reduce this burden and to come to a more accurate diagnosis at the very onset of the disease. Many have speculated that non-motor symptoms could provide a breakthrough in the quest for early biomarkers of Parkinson's disease, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 153 publications
(264 reference statements)
6
94
3
3
Order By: Relevance
“…Nevertheless, in contrast with what happens in the brain, previous studies had not found phosphorylated α-synuclein deposits within retinal dopaminergic cells in patients suffering from PD. 2,3,61 We and others have always found scarce and sparse retinal phosphorylated α-synuclein deposits in the ganglion cell layer, and never within dopaminergic cells. This finding suggests that dopaminergic cell death in the retina is independent of a self-accumulation of phosphorylated α-synuclein or that the levels of phosphorylated α-synuclein are low and the techniques used are not able to detect it.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, in contrast with what happens in the brain, previous studies had not found phosphorylated α-synuclein deposits within retinal dopaminergic cells in patients suffering from PD. 2,3,61 We and others have always found scarce and sparse retinal phosphorylated α-synuclein deposits in the ganglion cell layer, and never within dopaminergic cells. This finding suggests that dopaminergic cell death in the retina is independent of a self-accumulation of phosphorylated α-synuclein or that the levels of phosphorylated α-synuclein are low and the techniques used are not able to detect it.…”
Section: Discussionmentioning
confidence: 90%
“…Among them, the retina has been recently proposed to reflect the PD brain pathology: phosphorylated α-synuclein deposits, similar to Lewy bodies, have been found in the retina of PD patients, whose density correlated with disease severity. 2,3 In addition, PD patients present several visual symptoms, such as reduced amplitudes in b-waves and oscillatory potentials on electroretinograms (ERGs), reduced visual evoked potentials, inner retinal layer thinning by optical coherence tomography (OCT), 4 impaired motion perception, contrast sensitivity, and color discrimination, [5][6][7][8] circadian rhythm dysfunction, 9,10 and melanopsin-containing retinal ganglion cell (mRGC) degeneration. 11 Considering the described similarities between the neurodegenerative process in the retina and brain, it is natural to wonder whether the dopaminergic cells in the retina are involved in the disease as they are in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…αSYN, as native monomeric inclusions, has been found in the retina of HCs, where it could play a role into neurotransmission, synaptic plasticity, and vesicle trafficking (39). Instead, phosphor-αSYN has been found only in PD patients' retina, just within the somata and neurites of RNFL, GCL, and IPL (40,41). Thus, it has been supposed that visual impairment reported in PD may be due to dopamine depletion and α-synuclein accumulation in the retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accumulating experimental evidence suggests that pathological α-Syn aggregates are present in the retina and/or visual system of PD patients and of PD animal models. In addition, phosphorylated α-Syn accumulates in the retina as well as in the brain also at early stages, preceding the appearance of clinical signs of parkinsonism or dementia (Guo et al, 2018;Ortuno-Lizaran et al, 2018;Veys et al, 2019). Visual symptoms are probably the least invalidating symptoms in PD and DLB but they are being seriously considered as significant disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%